Detection of lipid in atherosclerotic vessels using ultrasound-guided spectroscopic intravascular photoacoustic imaging - Wang, Bo (Optical Society of America, 2010)
Lipid is a common constituent in atherosclerotic plaques. The location and area of the lipid region is closely related to the progression of the disease. Intravascular photoacoustic (IVPA) imaging, a minimally invasive imaging modality, can spatially resolve the optical absorption property of arterial tissue. Based on the distinct optical absorption spectrum of fat in the near infrared wavelength range, spectroscopic IVPA imaging may distinguish lipid from other water-based tissue types in the atherosclerotic artery. In this study, a bench-top spectroscopic IVPA imaging system was used to ex-vivo image both atherosclerotic and normal rabbit aortas. By combing the spectroscopic IVPA image with the intravascular ultrasound (IVUS) image, lipid regions in the aorta were identified. The results demonstrated that IVUS-guided spectroscopic IVPA imaging is a promising tool to differentiate lipid in atherosclerosis.